The burden of physical inactivity for the public health care system in Brazil - Eliza Prodel; Matías Mrejen; Pedro Augusto de Carvalho Mira; Jorge Britto; Marco Antonio Vargas; Antonio Claudio Lucas Nobrega (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To update the estimated cost of physical inactivity for the Brazilian Unified Health System (SUS). METHODS The hospitalization costs were accessed via a database of the Ministry of Health - Informatics Department of the Brazilian SUS. Physical inactivity for the year 2017 was accessed via the Sistema de Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (Vigitel - Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey). Seven chronic non-communicable diseases (NCD) were selected via the international classification of disease (ICD-10). The population fraction attributable to physical inactivity was calculated based on relative risk reported in previous studies and the prevalence of physical inactivity. RESULTS In 2017, the seven NCD considered in the analysis were responsible for 154,017 hospital admissions in adults older than 40 years old, residing in the state capitals and the Federal District, which corresponded to 6.5% of hospitalizations and 10.6% of SUS costs at an estimated US$ 112,524,914.47. Considering the group of individuals with insufficient physical activity in their leisure time, the percentage cost attributed to physical inactivity reached 17.4% of the estimated costs with NCD. At a national level, NCD were responsible for approximately 740 thousand hospitalizations, costing US$ 482 million, from which 17.4%, US$ 83 million were attributed to physical inactivity. CONCLUSION This study provides evidence to conclude that physical inactivity exerts an economic impact on the SUS due to NCD hospitalization. Physical inactivity is a modifiable lifestyle and compelling evidence, including that of this article, supports the promotion of a more active community as one of the major targets of public health care policies.